Oncolytic effect of SARS-CoV2 in a patient with NK lymphoma: Spontaneous remission in NK/T-cell Lymphoma during Covid-19 - Pasin, Federico; Mascalchi Calveri, Matteo; Calabrese, Alberto; Pizzarelli, Ginevra; Bongiovanni, Isabel; Andreoli, Michele; Cattaneo, Chiara; Rignanese, Giovanni (Acta Biomedica Atenei Parmensis, 2020)
Covid-19 infection was a possible causal factor in the exhaustion and decrease number of NK clonal cells, resulting in a evident improvement of signs, symptoms and clinical features related to NK lymphoma refractory to previous immuno-chemiotherapy. It has been shown that SARS-CoV2 binds to ACE2. Covid-19 may infect NK cells to suppress their functions, as NK cells express angiotensin converting enzyme 2 (ACE2). The excessive production of proinflammatory cytokines in Covid-19 infection may have played a crucial role in lymphodepletion. Although not published in Covid-19, other RNA viruses that cause acute pulmonary infections promote NK cell apoptosis. In NK/T-cell lymphoma plasma EBV-DNA is a sensitive surrogate biomarker of lymphoma load. In this case, we also notice a dramatic transient reduction in plasmatic EBV-DNA viral copies during Covid-19 pneumonia other than NK clonal cells reduction, and after the infection resolution we described a lymphoma relapse as well as EBV-DNA increase and the rising in NK clonal cells count.Although the mechanism leading to spontaneous remission remain uncharacterized, we hypothezised that a favorable adaptive immunity against concurrent viral infection could render an enhanced anti-tumor effect. We suppose COVID-19 infection have induced a transient remission in this patient affected with NK neoplasm.